Establishing viable and sustainable rural economic development programmes in a competitive global economy : analysis of marula commercialisation in South Africa - Mahlait, Vuyo F. (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.